2006
DOI: 10.1103/physreva.74.063402
|View full text |Cite
|
Sign up to set email alerts
|

Probing ultracold collisional dynamics with frequency-chirped pulses

Abstract: We report on the dynamics of ultracold collisions induced by near-resonant frequency-chirped light. A series of identical chirped pulses, separated by a variable delay, is applied to an ultracold sample of 85 Rb, and the rate of inelastic trap-loss collisions is measured. For small detunings of the chirped light below the atomic resonance, we observe that the rate of collisions induced by a given pulse can be increased by the presence of an earlier pulse. We attribute this to the enhancement of short-range col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Multiple-pulse effects were also investigated. We found that the rate of collisions induced by a given pulse can be enhanced or suppressed by a preceding pulse, depending on the delay [30]. In work most relevant to that described here, we demonstrated coherent control of these ultracold trap-loss collisions [31].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Multiple-pulse effects were also investigated. We found that the rate of collisions induced by a given pulse can be enhanced or suppressed by a preceding pulse, depending on the delay [30]. In work most relevant to that described here, we demonstrated coherent control of these ultracold trap-loss collisions [31].…”
Section: Introductionmentioning
confidence: 55%
“…The MOT light is turned off for 150 µs, during which time a number (typically 60) of frequency-chirped pulses with peak intensity I = 67 W/cm 2 illuminates the atoms at a repetition rate of 1 MHz. This 1-µs delay between pulses ensures that each chirped pulse acts independently [30]. The overall sequence is repeated every 722 µs.…”
Section: Methodsmentioning
confidence: 99%
“…Trapping rubidium in an optical lattice has facilitated studies of atom-molecule dark states [10] and transferring the molecules into their vibrational ground state [11]. The Rb 2 molecule continues to draw attention in the context of the coherent control of ultracold collisions [12][13][14][15][16] and femtosecond photoassociation [17][18][19][20]. These experiments as well as those employing photoassociation with continuous wave lasers [21][22][23][24][25] require precise spectroscopic knowledge not only of the ground but also the excited states for both interpretation and detection.…”
Section: Introductionmentioning
confidence: 99%
“…the efficiency of the pump step. While Feshbach-optimized photoassociation [39] is limited to the odd isotopes of strontium, flux enhancement via coherent control of ultracold collisions [40,41,42] could represent a general means of pushing the atom pairs closer together before photoassociating them.…”
Section: Discussionmentioning
confidence: 99%